2020
DOI: 10.1007/s13555-020-00352-4
|View full text |Cite
|
Sign up to set email alerts
|

A Calm, Dispassionate Look at Skin Microbiota in Atopic Dermatitis: An Integrative Literature Review

Abstract: Atopic dermatitis (AD) is a chronic common inflammatory skin disorder with clinical characteristics of pruritic, dry, and recurrent flares that involve the whole body. Recent studies have demonstrated that the skin microbiota, characterized by an overgrowth of Staphylococcus aureus (S. aureus), plays a critical role in the manifestation of AD. There is striking evidence that skin microbiota can modulate the development and progression of AD. Therefore, more and more therapeutic approaches are adopted for modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
2
12
0
1
Order By: Relevance
“…Compared with the control group, patients with AD had S aureus colonized in lesions, but less Cutibacterium , Streptococcus , Acinetobacter, and Corynebacterium 24,25 . Early clinical studies have shown that topical application of symbiotic bacteria, such as Staphylococcus hominis or Roseomonas mucosa , can assist in the treatment of atopic dermatitis, which supports the important role of symbiotic bacteria in reducing S aureus colonization in patients with atopic dermatitis 26 …”
Section: Changes Of Skin Microbial Community In Inflammatory Skin Dismentioning
confidence: 78%
See 1 more Smart Citation
“…Compared with the control group, patients with AD had S aureus colonized in lesions, but less Cutibacterium , Streptococcus , Acinetobacter, and Corynebacterium 24,25 . Early clinical studies have shown that topical application of symbiotic bacteria, such as Staphylococcus hominis or Roseomonas mucosa , can assist in the treatment of atopic dermatitis, which supports the important role of symbiotic bacteria in reducing S aureus colonization in patients with atopic dermatitis 26 …”
Section: Changes Of Skin Microbial Community In Inflammatory Skin Dismentioning
confidence: 78%
“…24,25 Early clinical studies have shown that topical application of symbiotic bacteria, such as Staphylococcus hominis or Roseomonas mucosa, can assist in the treatment of atopic dermatitis, which supports the important role of symbiotic bacteria in reducing S aureus colonization in patients with atopic dermatitis. 26 In psoriasis, Chang H W et al believed that the proportion of S aureus was closely related to the lesions of psoriasis, and the ratio of S epidermis and Cutibacterium acnes(C acnes) in lesions was lower than that in healthy skin. 13…”
Section: Skin Microbiota Dysbiosis In Inflammatory Skin Diseasesmentioning
confidence: 99%
“…These diverse communities of bacteria, fungi, mites and viruses can provide protection against disease and form dynamic, yet distinct niches on the skin (Oh, Byrd et al 2014). Increasing evidence has associated altered microbial communities or dysbiosis in the skin with cutaneous diseases (Oh, Freeman et al 2013, Weyrich, Dixit et al 2015), especially atopic dermatitis (Grice 2014, Powers, McShane et al 2015, Wan and Chen 2020). New strategies have emerged using microbes as therapy for treating a range of diseases (Dreher-Lesnick, Stibitz et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These diverse communities of bacteria, fungi, mites, and viruses can provide protection against disease and form dynamic, yet distinct, niches on the skin (9). Increasing evidence has associated altered microbial communities or dysbiosis in the skin with cutaneous diseases (8,10), especially atopic dermatitis (11)(12)(13). New strategies have emerged using microbes as therapy for treating a range of diseases (14).…”
mentioning
confidence: 99%